SOSIALISASI PEMANFAATAN TEKNOLOGI AUGMENTED REALITY (AR) SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF BAGI GURU TK/TPA NURUL IMAN PANNARA - Fattah, Farniwati; Sugiarti, Sugiarti; Wahab, Abdul; Irawati, Irawati; Nurul, Besse; Bora, Leni J; Munawir, Munawir (Universitas Mataram, 2025)
The digital transformation in education has encouraged the integration of technology-based media to create more interactive learning environments, especially at the early childhood education level. One of the main challenges faced by teachers in TK/TPA is delivering abstract materials such as hijaiyah letters in an engaging and comprehensible manner. The lack of varied teaching media has contributed to low student interest and participation in learning. Augmented Reality (AR) technology offers a promising solution by presenting learning materials in a more visual, concrete, and contextual format. This community engagement program aimed to enhance the understanding and awareness of TK/TPA Nurul Iman Pannara teachers regarding the use of AR as an interactive learning medium for hijaiyah instruction. The method involved preliminary observations, problem formulation, material preparation, and face-to-face implementation, including pre-tests and post-tests to evaluate participants’ comprehension levels. The results showed an increase in the average score from 3.15 (moderate understanding) to 4.01 (good understanding) after the activity. Teachers demonstrated high enthusiasm, actively participated in discussions, and expressed interest in further training for AR implementation. Positive responses also emerged regarding the potential of AR to improve the quality of instruction and student engagement. The documentation reflected strong involvement from participants and a collaborative learning atmosphere. In conclusion, the socialization activity effectively enhanced teachers’ digital literacy and opened opportunities for sustainable AR implementation in Islamic early childhood education settings.